Use of Zoom-Based Learning Media to Increase Interest in Learning During the Covid-19 Pandemic - Erfa Okta Lussianda; Nia Anggraini; Liga Febrina (Husnayain Business Review, 2021)
The purpose of this study was to find out to what extent online-based learning media (Zoom) can create student interest in STIE Persada Bunda in learning.This research was conducted for 1 (one) year starting from June 2020 to August 2021. The sample and this research were 87 samples, using the techniquestratified proportional random sampling. .The results found that online learning media (zoom) has an effect on student learning interest, this shows that the better the media provided by the lecturer, the more interested students are in learning by lecturers in the teaching and learning process. If the learning media is more interesting, the student's interest in learning will increase.